Oral glucose-lowering drugs and long-term risk of benign prostatic hyperplasia - Stanislav N. Volkov; Robert K. Mikheev; Olga R. Grigoryan; Vitaliy I. Tereshchenko; Vladimir S. Stepanchenko; Elena N. Andreeva (Consilium Medicum)
Background. One of the most prominent threats for masculine health is comorbidity between benign prostatic hyperplasia (BPH) and diabetes mellitus type 2. Many publications suppose influence of hyperglycemia on lower urinary tract obstruction. Question about influence of the most common oral glucose-lowering drugs – biguanides (metformin hydrochloride) and third-generation sulfonylurea (glimepiride) has not been answered yet.